ØªÙ†Ù…ÙŠØ© ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„Ù…Ù„ØµÙ‚ Ø§Ù„ÙÙƒØ§Ù‡ÙŠ ÙÙŠ ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¦Ø© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Ruwaida Hudatullah (Lughatu Ad-Dhat, 2020)
ABSTRACT This research aims to develop correct and effective humorous poster methods on Arabic materials. The method used in this research is research and development with reference to the Borg and Gall development model with seven stages, viz., Research and data collection, planning, product development, expert validation testing, product review, product trial, and final product review. Based on the research results, it showed that the Arabic comic poster product is suitable for use in learning. In the results of the media experts' validation, it is known that the comic poster product is rated